2020
DOI: 10.3390/d12030113
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Rotifer Community to Microhabitat Changes Caused by Summer-Concentrated Rainfall in a Shallow Reservoir, South Korea

Abstract: Empirical studies suggest that the structural heterogeneity of aquatic ecosystem microhabitat is determined by the diversity and abundance of macrophytes. However, excessive accumulation of free-floating macrophytes on the water surface can reduce the biomass of submerged macrophytes, resulting in a relatively simplified habitat structure. We hypothesized that heavy summer rainfall disrupts the growth of free-floating macrophytes covering much of the Jangcheok Reservoir’s water surface, thereby resulting in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Most of the remaining wetlands and reservoirs were artificially constructed. Rainfall in South Korea is concentrated in summer [45] and relatively low in the other seasons, making it relatively difficult to secure water resources. Therefore, wetlands or reservoirs were artificially created around farmland or residential areas.…”
Section: Effects Of Environmental Characteristics On the Settlement Of Exotic Fish In Freshwater Wetlandsmentioning
confidence: 99%
“…Most of the remaining wetlands and reservoirs were artificially constructed. Rainfall in South Korea is concentrated in summer [45] and relatively low in the other seasons, making it relatively difficult to secure water resources. Therefore, wetlands or reservoirs were artificially created around farmland or residential areas.…”
Section: Effects Of Environmental Characteristics On the Settlement Of Exotic Fish In Freshwater Wetlandsmentioning
confidence: 99%
“…The majority of this area has a poor drainage capacity and is covered with a large number of wetlands owing to flooding by the Nakdong River in southeastern South Korea or major tributary streams. Summer-concentrated rainfall leads to frequent flooding in the region and negatively affects the distribution and population growth of various biological communities [ 42 ]. However, in other seasons (spring, autumn, and winter), when less rainfall occurs, a relatively stable environment is maintained.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies suggested that a high abundance of aquatic macrophytes generally leads to habitat stabilization against physical disturbances, such as flow fluctuations and large amounts of summer rainfall. Ecosystems rich in aquatic macrophytes can consequently support a high density and diversity of invertebrates (e.g., rotifers [9,54]). In the present study, we observed high densities of Odonata larvae in wetlands where aquatic macrophytes were abundant.…”
Section: Influence Of Environmental Variables On Odonata Larvae Distributionmentioning
confidence: 99%
“…However, these macrophytic species are suitable habitats for damselflies, which move by crawling along solid stems [5]. Such niche partitioning allows species to Insects 2020, 11, 273 2 of 18 coexist and fosters species diversity [6][7][8][9]. Therefore, the distribution patterns and habitat preferences of invertebrates should be identified in order to elucidate determinants of community structure.…”
Section: Introductionmentioning
confidence: 99%